Thermally stable passivation toward high efficiency inverted perovskite solar cells - Oliver, RDJ; Lin, Y-H; Horn, AJ; Xia, CQ; Warby, JH; Johnston, MB; Ramadan, AJ; Snaith, HJ (American Chemical Society, 2020)
Although metal halide perovskite photovoltaics have shown an unprecedented rise in power conversion efficiency (PCE), they remain far from their theoretical PCE limit. Among the highest efficiencies to date are delivered when polycrystalline films are enhanced via “molecular passivation”, but this can introduce new instabilities, in particular under severe accelerated aging conditions (e.g., at 85 °C in the dark or under full spectrum simulated sunlight). Here, we utilize a benzylammonium bromide passivation treatment to improve device performance, achieving the champion stabilized power output (SPO) of 19.5 % in a p-i-n device architecture. We correlate the improved device performance with a significant increase in charge carrier diffusion lengths, mobilities, and lifetimes. Furthermore, treated devices maintain an increased performance during 120 h combined stressing under simulated full spectrum sunlight at 85 °C, indicating that enhancement from this passivation treatment is sustained under harsh accelerated aging conditions. This is a crucial step toward real-world operation-relevant passivation treatments.